Validity study of the Three-Dimensional Work Fatigue Inventory among higher education nursing faculty - Évilin Diniz Gutierres Ruivo; Laurelize Pereira Rocha; Jamila Geri Tomaschewski-Barlem; Graziele de Lima Dalmolin; Laís Farias Juliano; Janaína Cassana Mello Yasin (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to adapt and validate the Three-Dimensional Work Fatigue Inventory (3D-WFI) for Brazil's cultural reality and assess the psychometric properties. Methods: a methodological study developed in six stages: initial translation; synthesis of translations; back translation; review by expert committee; pretest; and review of the adaptation process by the researchers. For validity, the instrument was applied to a sample of 318 nursing professors from Brazilian federal and state public universities. Data were analyzed using exploratory and confirmatory factor analysis, composite reliability and instrument reliability (Cronbach's alpha and McDonald's omega). Results: the 3D-WFI instrument showed excellent internal consistency (α=0.95 and ω=0.97), three dimensions and explained variance of 62.77%. Conclusions: the Brazilian version of the instrument showed excellent psychometric properties for assessing fatigue among Brazilian workers.